Uji Coba Sistem Pneumatik pada Hand Trainer Berbahan TPU untuk Meningkatkan Fungsi Motorik Tangan Pasien Strok - Yogi Ilyasyah; Hasdiansah Hasdiansah (Jurnal Inovasi Teknologi Terapan, 2026)
This study focuses on designing and testing a Pneumatic Hand Trainer using 3D printing technology to support hand rehabilitation for post-stroke patients. The device employs a soft actuator made of Thermoplastic Polyurethane (TPU) driven by compressed air through a pneumatic system. The experimental process included design using SolidWorks, 3D printing fabrication, assembly, and performance testing. The results showed that the device operated effectively at a pressure range of 0.39–0.45 MPa, with an average of 0.4 MPa, providing stable and responsive motion during grip and release movements. Minor pressure variations were within acceptable limits, influenced by air supply and material elasticity. Overall, the system is efficient, safe, and capable of simulating natural finger motion, indicating its potential as a cost-effective rehabilitation tool based on additive manufacturing and pneumatic actuation.